Study the Characteristics of Lactic Acid Bacteria Isolated from Human Milk as a Probiotic in Vitro (Eurasian Medical Research Periodical, 2023)
Probiotics are live microorganism preparations that benefit their host's health. Although probiotic strains can be isolated from a variety of sources, human origin is the primary requirement for human applications. Milk and other dairy products are generally regarded as primary food sources for LAB. After being taken from human breast milk and put through a biochemical test at AlZahra Teaching Hospital in Wasit Province, Iraq, a total of 50 samples produced favorable findings. The tolerance of LAB isolates in simulated gastric juice and antimicrobial activity against pathogenic bacteria (Escherichia coli and Staphylococcus aureus) were studied by using the well diffusion method. 50 positive samples for LAB isolates were identified by PCR (16S rRNA sequencing) and were catalase-negative. LAB isolates have shown tolerance for simulated gastric juice. The average viable cell count of LAB varied significantly (P≤ 0.01) among the fifty samples, falling from 4.949 ± 0.043 log cycles CFU/mL at zero time (before the incubation time) at pH 2.0 to 4.055 ± 0.087 log cycles CFU/mL after the incubation period (after 3 hours) at 37oC and pH 2.0. Additionally, the LAB isolates demonstrated a significant difference between the inhibition zone of S. aureus Gram positive and the inhibition zone of E. coli Gram negative (P≤ 0.01). LAB isolates under study show support for probiotic properties, and the value of breastfeeding over bottle feeding is demonstrated